Epidemiological Study and Spatial Modeling of Cutaneous Leishmaniasis in Bushehr Province using the Geographic Information System (GIS) during 2011-2015 - Ali Dehghani; Mohamad Hasan Lotfi; Hossein Falahzadeh; Katayon Vahdat; Zahra Shabani (Shahid Sadoughi University of Medical Sciences, 2019)
Introduction: It is generally accepted that cutaneous leishmaniasis is an important health problem in the world which is caused by leishmaniasis protozoan. This disease is also considered as a health problem in some regions of Iran including Bushehr province. The present study investigated the geographical dispersion and epidemiological characteristics of subjects with the cutaneous leishmaniasis in this province during 2011-2015. Methods: In this cross-sectional and analytical study, the epidemiologic data including the age, gender, residential area, and counties with this disease was analyzed and collected from 663 patients who were followed up and treated during 2011 to 2015. Results: 422 (63.7%) of studied people were residents of urban areas and 241 (36.3%) lived in rural areas. 59.4% (394 people) were male and 40.6% (269) were female. The mean age of subjects was 21.91± 17.01 (ranging from 1 to 80 years). Kangan County with an average 5-year incidence of 17.72 per a hundred thousand people had the highest incidence, but Tangestan County with the incidence of 8.47 per a hundred thousand people had the lowest average incidence. Based on GIS results, Jam County, which was not recognized as the focus of this disease in the past, has been considered as a new focus of disease in recent years. Conclusion: The geographic information system (GIS) is an effective tool for the organization of diseases and health data. The crisis can be identified and controlled by taking proper measures with the discovery of spatial accumulation of diseases.